Market imperfections for tractor service provision in Nigeria: International perspectives and empirical evidence - Takeshima, Hiroyuki (International Food Policy Research Institute, 2015)
In order to distinguish the impacts of technology adoption at the extensive margin from those at the intensive margin, in the empirical analyses we tested these hypotheses focusing on the differences among marginal adopters of tractor hiring services and nonadopters of similar characteristics. The results are two-fold: (1) adoptions patterns of tractor services are partly explained by basic factor endowments, suggesting that the market for custom hiring is in some way functioning efficiently in response to economic conditions; (2) adoptions are, however, affected by supply-side factors including the presence of large farm households (and thus potential tractor owners) within the district, and (3) per capita household expenditure level differs significantly between the marginal adopters and nonadopters of similar characteristics. This difference seems to arise from the adoption per se, rather than the intensity of adoption, which is consistent with the hypothesis of the imperfection of the custom hiring market.